2002
DOI: 10.1002/j.1556-6678.2002.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Ways of Measuring Counselees' Jungian Psychological‐Type Preferences

Abstract: Instruments measuring Carl Jung's (1921/1971) theory of psychological types have been widely used in various counseling contexts, including career counseling, marital and family therapy and team building. The most popular measure of types, the Myers‐Briggs Type Indicator (MBTI), was developed by Katherine C. Briggs and her daughter, Isabel Briggs Myers, but the MBTI has been criticized for (a) dichotomous scoring, (b) forced‐choice response formats, and (c) differential gender weighting of item responses. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…It has been suggested that Jungian-type differences appear in educational aptitude, application, interest, and achievement and that "type theory accounts for the different aspects of these characteristics" (Myers & McCaulley, 1985, p. 95). To overcome difficulties with the most commonly used measure of Jungian types (Vacha-Haase & Thompson, 2002), here the Personal Preferences Self-Description Questionnaire (PPSDQ) was used to measure these preferences (Arnau, Thompson, & Rosen, 1999;Kier, Melancon, & Thompson, 1998;Melancon & Thompson, 1996;Mittag, 1999).…”
Section: Research Questionsmentioning
confidence: 99%
“…It has been suggested that Jungian-type differences appear in educational aptitude, application, interest, and achievement and that "type theory accounts for the different aspects of these characteristics" (Myers & McCaulley, 1985, p. 95). To overcome difficulties with the most commonly used measure of Jungian types (Vacha-Haase & Thompson, 2002), here the Personal Preferences Self-Description Questionnaire (PPSDQ) was used to measure these preferences (Arnau, Thompson, & Rosen, 1999;Kier, Melancon, & Thompson, 1998;Melancon & Thompson, 1996;Mittag, 1999).…”
Section: Research Questionsmentioning
confidence: 99%
“…Therefore, it is a common personality instrument that is utilized by two million users each year (Furnham, Moutafi, & Crump, 2003). Vacha-Haase and Thompson (2002) summarized the popularity of MBTI as being due to the fact that it focuses on normal variations in personality and the fact that it is value neutral. In addition, Myers, McCaulley, Quenk, and Hammer (1998) reviewed previous studies associated with the MBTI and concluded that the MBTI showed acceptable reliabilities and validities (detailed in the Method Section).…”
Section: Introductionmentioning
confidence: 99%
“…In addition Keirsey reports on his website that the KTS has a 0.75 correlation with the MBTI (Keirsey, website 2002). Both measures are widely used in career assessment situations (Vacha-Haase & Thompson, 2002). Dodd and Bayne (2007) found adequate reliabilities of the KTSII for research purposes of 0.78 (EI), 0.79 (SN), 0.70 (TF) and 0.73 (JP).…”
Section: Instrumentsmentioning
confidence: 99%